2006
DOI: 10.1038/emm.2006.58
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of CD8+T-cell anergy by CD4+CD25+ regulatory T cells in chronic graft-versus-host disease

Abstract: In a murine model of systemic lupus erythematosus (SLE)-like chronic graft-versus-host disease (cGVHD), donor CD8 + T cells rapidly fall into anergy to host cells, while donor CD4 + T cells hyperactivate B cells and break B-cell tolerance to self-Ags in the recipient mouse. The functional recovery of donor CD8 + T cells can result in the conversion of cGVHD to acute GVHD (aGVHD), indicating that donor CD8 + T-cell anergy is a restriction factor in the development of cGVHD. In this report, we present evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…72 Additional studies have demonstrated that depletion of regulatory cells under conditions of chronic GVHD converts the disease to the acute form, coincident with expansion of CD8 ϩ T cells, suggesting that regulatory cells preferentially suppress CD8 ϩ T-cell responses. 46 Our results are consistent with these data because transfer of mATG-induced regulatory cells inhibits acute GVHD and is associated with suppressed CD8 ϩ T-cell expansion. Thus, regulatory cell induction and/or transfer might be particularly useful in disease settings mediated or contributed to by CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…72 Additional studies have demonstrated that depletion of regulatory cells under conditions of chronic GVHD converts the disease to the acute form, coincident with expansion of CD8 ϩ T cells, suggesting that regulatory cells preferentially suppress CD8 ϩ T-cell responses. 46 Our results are consistent with these data because transfer of mATG-induced regulatory cells inhibits acute GVHD and is associated with suppressed CD8 ϩ T-cell expansion. Thus, regulatory cell induction and/or transfer might be particularly useful in disease settings mediated or contributed to by CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 82%
“…Because cytotoxic CD8 ϩ T cells are important for the direct tissue damage and acute manifestations of GVHD under conditions of disparities in both MHC class I and II loci, 44,45 the depletion of or suppression of the expansion and/or activity of CD8 ϩ T cells is beneficial in reducing disease symptoms. [44][45][46] These data indicate that the transfer of in vitro mATG-treated cells results in inhibition of allogeneic CD8 ϩ T-cell expansion. There were no detectable effects of the mATG-treated splenocytes on CD4 ϩ T-cell percentages in the blood at any time point, however, it remains possible that depressed functional activity of CD4 T cells is responsible for limiting the CD8 ϩ T-cell expansion and decreased disease manifes- Figure 6.…”
Section: Adoptive Transfer Of In Vitro Matg-treated Mouse Spleen Cellmentioning
confidence: 78%
“…Interestingly, depletion of donor CD4 ϩ T cells, regardless of whether anti-CD40 mAb or control Ig was administered, induced significant levels of host cell deletion, in particular, host B cells but not donor cell engraftment. This phenomenon might occur because of the absence of donor regulatory CD4 ϩ T cells that regulate donor CD8 ϩ T cell anergy in cGVHD (39). As expected, basal levels of autoantibody were produced in mice that received donor cells depleted of CD4 ϩ T cells (Table III).…”
Section: Donor Cd4 ϩ T Cells and Anti-cd40 Mab Have A Synergistic Effsupporting
confidence: 53%
“…Thus, there is a notion that the frequencies of donor alloreactive CD8 + T cells may determine whether aGvHD or cGvHD develops. For example, CD8 + T cell anergy can shift the responses from an aGvHD to an SLE-like cGvHD (194, 213). Although CD8 + T cells are not necessary to induce cGvHD, they infiltrate skin and intestines where they contribute to the observed pathology (214).…”
Section: Chronic Gvhdmentioning
confidence: 99%